Gender dan Transformasi Pendidikan Islam dalam Tradisi Melayu: Kajian Literatur Kritis - Fitriyanti Fitriyanti; Rahayu Suprati; Abdullah Idi; Abdillah Asmara (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
This article examines gender relations and the transformation of Islamic education within Malay tradition. The study aims to analyze how Malay cultural values interact with Islamic educational reform and how gender relations are constructed, maintained, and transformed in educational institutions and community-based religious learning spaces. Using a qualitative library research design, this study reviews recent academic literature, policy-related documents, and conceptual studies on gender, Islamic education, and Malay culture published mainly between 2018 and 2026. Data were collected through documentation, literature tracing, and thematic note-taking, then analyzed using content analysis and descriptive-critical interpretation. The findings reveal that Islamic education in Malay society is undergoing a gradual transformation from traditional, male-dominated authority structures toward more adaptive, inclusive, and socially responsive educational practices. Women's access to Islamic education and participation in social-religious activities have increased, yet gender inequality persists in leadership, institutional authority, curriculum representation, and decision-making. The study further shows that Malay tradition does not necessarily obstruct gender justice; values such as deliberation, respect for knowledge, communal harmony, and public benefit can serve as cultural capital for developing gender-responsive Islamic education. The novelty of this article lies in positioning Malay tradition not merely as a cultural background but as an analytical framework for negotiating gender justice within Islamic education. The study implies the need for curriculum reconstruction, gender-sensitive teacher capacity building, expanded women's leadership, and stronger collaboration between Islamic educational institutions, families, and Malay customary communities.